Examining the Perceptions of Professional Accountants towards the Financial Reporting Standard for Large and Medium Sized Enterprises: The Case of Elazig Province - Demir, Özcan; Narlıkaya, Zülküf (Fırat University, 2021)
Accounting With this study, it is aimed to determine the perception levels of the accounting professionals operating in Elazig Province regarding the Financial Reporting Standard for Large and Medium Sized Enterprises (BOBI FRS) in terms of different variables. The population of the research consists of accounting professionals operating in the province of Elazig. The sample consists of 156 randomly selected accounting professionals representing the universe. In this study, the quantitative research method has been used and the data were obtained by using the survey method. Data related to the study were analyzed with the licensed SPSS-22.0 program. In this study, The main statistical analyses used are descriptive statistics, validity and reliability analysis, independent t-test and one-way Anova. As a result of the study, it has been determined that the perceptions of professional accountants towards BOBI FRS differ significantly in terms of gender, age, having a BOBI FRS taxpayer and receiving BOBI FRS training.

Bu çalışma ile Elazığ ilinden faaliyet yürüten muhasebe meslek mensuplarının Büyük ve Orta Boy İşletmeler için Finansal Raporlama Standardına (BOBİ FRS) yönelik algı düzeylerinin farklı değişkenler açısından tespit edilmesi amaçlanmıştır. Çalışmanın evrenini Elazığ ilinde faaliyet gösteren muhasebe meslek mensupları oluşturmaktadır. Çalışmanın örneklemini evreni temsilen tesadüfi seçilen 156 meslek mensubu oluşturmuştur. Çalışmada nicel araştırma yöntemi kullanılmış ve veriler anket yöntemi kullanılarak elde edilmiştir. Çalışmaya ilişkin veriler lisanslı SPSS-22.0 programı ile analiz edilmiştir. Çalışmada kullanılan başlıca analizler; betimleyici istatistikler, geçerlilik ve güvenilirlik analizleri, bağımsız t-testi ve tek yönlü (Anova) varyans analizi şeklindedir. Çalışma sonucunda muhasebe meslek mensuplarının BOBİ FRS’ye yönelik algıları cinsiyet, yaş, BOBİ FRS mükellefine sahip olma ve BOBİ FRS eğitimi alma değişkenleri açısından anlamlı farklılık gösterdiği tespit edilmiştir.
MUHASEBE MESLEK MENSUPLARININ BÜYÜK VE ORTA BOY İŞLETMELER İÇİN FİNANSAL RAPORLAMA STANDARDINA YÖNELİK ALGILARININ İNCELENMESİ: ELAZIĞ İLİ ÖRNEĞİ